Career Advancement in Indonesian Academia A Concern of Gender Discrimination - Nur Kholis (Jurnal Kependidikan Islam, 2012)
The human resource management practices in the State Higher Education Irxstitutions (SHEls) in Indonesia follow the rules and regulations set by the government; this in theory should guarantee equality to all staff. In reality, however, the effects are different to female and male staff with regards to their career advancement. The present study aims to explore women's status in the structural and academic ranks as well as in the management and leadership positions compared to men's, and the reasons responsible for the gap in their career advancement. A set of instruments was distributed to universities u'iUing to participate in this study. Ten universities participated in this study by returning completed instruments. This study reveals that the representation of women in the higher structural and academic ranks was reasonably below than that of men. However, their number in the starting levels tended to grow. Women were also scarce in the top management and leadership positions, even though their representation in the lower levels tended to increase. Reasons for this disparity include women's lacking research and publication; tendency to recruit future male leaders; and the women's lower qualifications for the higher posts. The implication of this study is provided